Downregulation of Hlx Closely Related to the Decreased Expressions of T-bet and Runx3 in Patients with Gastric Cancer May Be Associated with a Pathological Event Leading to the Imbalance of Th1/Th2. (19th November 2012) - Xu, Yan; Gao, Jingjing; Su, Zhaoliang; Dai, Xiaoli; Li, Yazhen; Liu, Yingzhao; Chen, Jianguo; Tong, Jia; Zhang, Yun; Wu, Chaoyang; Zheng, Dong; Wang, Shengjun; et al.
Abstract : T-bet plays an important role in immunoregulation; it induces the differentiation of Th1 together with the homeobox transcription factor gene Hlx . Recent studies show that T-bet and Th1-associated factors are critical in regulating tumor development. However, the contributions of Hlx in the occurrence and development of cancer remain unknown. In this study, the Hlx, T-bet, Runx3, and IFN- γ were measured in PBMC from patients with gastric cancer and the correlation between Hlx and T-bet or IFN- γ was assessed. The expression levels of Hlx, T-bet, and IFN - γ were significantly decreased, and there was a positive correlation between Hlx and T-bet or IFN- γ . In addition, the Runx3 expression was also downregulated with the lower T-bet mRNA level. These results suggested that the decreased Hlx expression was closely associated with T-bet and Runx3 downregulations and may contribute to the development of gastric cancer.